Percutaneous pedicle screw for unstable spine fractures in polytraumatized patients: A report of two cases - Tan, B.B.; Chan, C.Y.W.; Saw, L.B.; Kwan, M.K. (2012)
Unstable spine fractures commonly occur in the setting of a polytraumatized patient. The aim of management is to balance the need for early operative stabilization and prevent additional trauma due to the surgery. Recent published literature has demonstrated the benefits of early stabilization of an unstable spine fracture particularly in patients with higher injury severity score (ISS). We report two cases of polytrauma with unstable spine fractures stabilized with a minimally invasive percutaneous pedicle screw instrumentation system as a form of damage control surgery. The patients had good recovery from the polytrauma injuries. These two cases illustrate the role of minimally invasive stabilization, its limitations and technical pitfalls in the management of unstable spine fractures in the polytrauma setting as a form of damage control surgery.